(untitled) (Journal on studies and research of academic knowledge, 2016)
This study determined the biodegradability of low-density polyethylene (LPDE) by the action of native bacteria in the landfill of the City of Encarnación. To do this research, low-density polyethylene samples of soil were taken from two areas of the landfill. Microorganisms present in the soil were adapted to produce biomass in controlled conditions using polyethylene powder and enriched environment as the source of growth. Once the adaptation time was reached, it was evaluated the biodegrading action of bacteria in the landfill on polyethylene using it as the only carbon source, which consisted of an aliquot of bacteria and the source of growth. The Effect of the native bacteria on the polyethylene was determined by the remaining weight [mg] of the heavy plastics pieces, which were weighed every 7 days for 35 days. As a result, after 35 days of experimental period it was detected that the native bacteria biodegraded 8.5% of low-density polyethylene. Bioaugmentation was performed with strains of Pseudomonas aeruginosa, whereas its presence was detected in an enriched environment, not providing any weight variation in comparison to the values acquired previously.